2018
DOI: 10.1093/cid/ciy379
|View full text |Cite
|
Sign up to set email alerts
|

Association of Cutibacterium avidum Colonization in the Groin With Obesity: A Potential Risk Factor for Hip Periprosthetic Joint Infection

Abstract: The groin, rather than the anterior thigh, showed colonization for C. avidum in obese patients. Further studies are needed to evaluate current skin disinfection and draping protocols for hip arthroplasty, particularly in obese patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 29 publications
2
15
0
Order By: Relevance
“…The concept of abundant colonization with multiple microorganisms in the hip region [14, 15] is expected to mainly apply to direct anterior incisions, as previously described in literature [19, 20]. Interestingly, in our cohort obese patients showed abundant colonization with multiple microorganisms as well, even though posterolateral incisions were used for implantation of the hip arthroplasties.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…The concept of abundant colonization with multiple microorganisms in the hip region [14, 15] is expected to mainly apply to direct anterior incisions, as previously described in literature [19, 20]. Interestingly, in our cohort obese patients showed abundant colonization with multiple microorganisms as well, even though posterolateral incisions were used for implantation of the hip arthroplasties.…”
Section: Discussionmentioning
confidence: 57%
“…Thirdly, the applied cefazolin dosage as antibiotic prophylaxis may not be sufficient to achieve adequate tissue concentrations in obese patients, especially in patients weighing more than 120kg or with a BMI >40kg/m 2 [1113]. Finally, obese patients have increased bacterial colonization of the skin compared with non-obese patients, particularly in the groin [14, 15]. Currently applied antibiotic prophylaxis may not provide full coverage for these microorganisms.…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, attention has been directed toward a plausible link between PJI and patients’ individual risk factors in addition to the surgical- and hospital-related factors. More recently, substantial studies regarding the patient-related risk factors for PJI, such as obesity [ 4 , 11 – 14 ], diabetes mellitus (DM) [ 14 – 17 ], male gender [ 18 ], rheumatoid arthritis (RA) [ 19 , 20 ], and pulmonary diseases [ 6 , 21 ], have been reported. However, the power of these studies may be impaired due to limited numbers of recruited patients, controversial results and range of potential risk factor studies.…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with previous finding [27,18], our data showed that patients with a BMI greater than 40, 35, o r 30 had a 3.64, 2.46, or 2.02-fo ld higher risk of PJI co mpared with those counterparts with less BMI, respectively. Obese patients are more prone to increased risk of PJI in the peri-operative setting, which may be attributed to prolonged operative and anesthetic time, higher risk of colonizat ion for C. avidum in the groin [11], longer hospital stay and high readmission rates within 30 days [9]. Besides, being obese is usually correlated with higher presence of other commod ities including metabolic syndrome, wound dehiscence, and heart disease [1].…”
Section: Discussionmentioning
confidence: 99%